Use of a Modified Chaining Procedure with Textual Prompts to Establish Intraverbal Storytelling - Valentino, Amber L. (Anal Verbal Behav, 2015)
Echoic, tact, and textual transfer procedures have been proven successful in establishing simple intraverbals (Braam and Poling Applied Research in Mental Retardation, 4, 279–302, 1983; Luciano Applied Research in Mental Retardation, 102, 346–357, 1986; Watkins et al. The Analysis of Verbal Behavior, 7, 69–81, 1989). However, these strategies may be ineffective for some children due to the complexity of the targeted intraverbals. The current study investigated the use of a novel procedure which included a modified chaining procedure and textual prompts to establish intraverbal behavior in the form of telling short stories. Visual prompts and rule statements were used with some of the participants in order to produce the desired behavior change. Results indicated that the procedure was effective for teaching retelling of short stories in three children with autism.